THE PREVALENCE OF PRESBYOPIA IN OPTOMETRY CLINIC FOR ONE YEAR - Ahmed, Morad Amir; Mahmud, Sarbast A. (Kurdistan Journal of Applied Research, 2017)
Presbyopia is a natural part of the aging process of the eye in which the loss of flexibility of the crystalline lens takes place over a number of years. This study aimed to determine the prevalence of presbyopia for all cases in the clinic of optometry in Erbil Technical Medical Institute for one year. During the study period optometric and ophthalmologic examinations were performed on all participants. Near vision was tested and corrected to the nearest 0.5 diopters. Presbyopia was defined as at least 1 line of improvement on a near visual acuity chart with an addition of a plus lens. presbyopic correction coverage was calculated and the results were analyzed using SPSS Program. A total of 750 participants’ records were evaluated. Of those, 450 cases were females and 300 cases were males. Two hundred-twenty –five (30 %) of patients were presbyopia. Fifty-one patients of presbyopic patients (22.66%) were with ages between 39-45 year, seventy-five patients (33.33%) were with ages between 46-50 year, forty patients (17.77%) were with ages between 51-55 year, seventeen patients (7.55%) were with ages between 56-60, thirteen patients (5.77%) were with ages between 61-65 year, twenty patients (8.88%) were with ages between 66-70 year, six patients (2.66%) were with ages between 71-76 year, three patients (1.33%) were with ages between 76-80 year. Our study is the first population-based investigation of presbyopia in Erbil Clinics, with the aim of determining the prevalence of presbyopia in the clinic of Optometry that it is a sample of Kurdistan Region population. The results of this study indicate that the presbyopia was a common problem of the vision in Erbil.